The effect of curvature angle of curved RC box-girder continuous bridges on their transient response and vertical pounding subjected to near-source earthquakes - Tamaddon, S.; Hosseini, M.; Vasseghi, A. (Elsevier Science Inc, 2020)
Among highway bridges, curved ones are very common at urban intersections and, generally, in limited urban spaces. However, such bridges are often involved in multiple vibrational behaviors, making them more sensitive to vertical components of ground motion due to their irregular geometry. The primary objective of this study has been to develop a theoretical approach using the relationships of structural dynamics to evaluate the effect of central curvature angle on the seismic response of curved bridges with rubber bearings subjected to strong vertical ground motions of near field earthquakes. In this regard, the continuous flexural/torsional beam-spring rod model, has been used to calculate vertical force and the effect of this force on the dynamic response of curved bridge components. The wave propagation in the form of harmonic functions is induced by changing the phase angle for piers, and the wave transfer functions are solved by using eigenfunctions. The results of numerical analyses show that the wave transient behavior leads to separation of the girder from the bearing along with the pounding of the girder returning back onto the bearing, and that in the curved bridges with different central angles, the phenomenon of vertical pounding would occur in the range of the bridge natural vibration period, and pounding intensity would be strongly dependent on seismic excitation scenarios. The results also show that with increase in the curvature angle of the girder, the girder's lateral displacement does not necessarily increase, while the increase in the girder's torsion is related to its curvature angle.
Keywords: Curved bridges; Vertical earthquake excitation; Vertical pounding; Transient response; Multiple pounding